2017
DOI: 10.1371/journal.pone.0178843
|View full text |Cite
|
Sign up to set email alerts
|

Lack of robustness of textural measures obtained from 3D brain tumor MRIs impose a need for standardization

Abstract: PurposeTextural measures have been widely explored as imaging biomarkers in cancer. However, their robustness under dynamic range and spatial resolution changes in brain 3D magnetic resonance images (MRI) has not been assessed. The aim of this work was to study potential variations of textural measures due to changes in MRI protocols.Materials and methodsTwenty patients harboring glioblastoma with pretreatment 3D T1-weighted MRIs were included in the study. Four different spatial resolution combinations and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 40 publications
1
44
0
Order By: Relevance
“…Furthermore, the choice and definitions of the textural analysis metrics vary widely and the evaluation techniques differ substantially, thus, rendering a comparison between studies almost impossible [260,297]. The need for standardization efforts in the field of textural analyses has been highlighted previously [260,298,299], and efforts are currently under way to address this challenge [260,[300][301][302].…”
Section: Multi-centre Standardizationmentioning
confidence: 99%
“…Furthermore, the choice and definitions of the textural analysis metrics vary widely and the evaluation techniques differ substantially, thus, rendering a comparison between studies almost impossible [260,297]. The need for standardization efforts in the field of textural analyses has been highlighted previously [260,298,299], and efforts are currently under way to address this challenge [260,[300][301][302].…”
Section: Multi-centre Standardizationmentioning
confidence: 99%
“…The possibility of using high-resolution MSOM to analyse tumour heterogeneity may create new opportunities for studying tumour heterogeneity in a more detailed manner. Indeed, MSOM fulfils one set of proposed requirements 49 for analysing three-dimensional variations in tumour properties: high spatial resolution (10-100 μm) and a unique contrast and feature set not available to other imaging modalities. The study suggests the potential of textural measures of spatial heterogeneity such as skewness and kurtosis for image-based analysis of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Both Waugh et al 72 and Mayerhoefer et al 13 found spatial resolution to be the most important factor affecting MRTA and that variability in TR/TE, sampling bandwidth, and number of excitations is not significant at higher resolution. However, Molina et al 73 found that several GLCM and GLRLM texture features computed on 3D segmentation of brain gliomas were not robust over different spatial resolution/matrix size and gray-level ranges. They found only entropy to be the most robust feature.…”
Section: Challenges and Future Directionsmentioning
confidence: 99%